The Effect of Daily Physical Activity on Increasing Physical Fitness and Academic Achievement of Elementary School - Achmad Chabibi Arif; Ali Maksum; Advendi Kristiyandaru (BIRCU, 2021)
Theoretically, physical activity can improve physical fitness and cognitive functions. Students who do regular physical activity are expected to have fitness and fitness at the same time as their cognitive function grows and develops so that their academic achievement increases. Unfortunately, as technology advances and lifestyle changes, children's physical activity is decreasing. Effectiveness in achieving learning objectives continuously along with the level of student fitness and decreased cognitive function improvement. This study aims to examine the effect of daily physical activity on increasing students' fitness and academic achievement. The research method used is quasi-experimental with a matching-only design. As a sample, 30 grade 5 students of SDN Pesanggrahan I, Kwanyar, Bangkalan. The sample was divided into two groups, 15 students in the experimental group and 15 students in the control group. The treatment was given for 8 weeks with 3 meetings per week. The fitness variable was measured by a multistage fitness test, meanwhile, the academic achievement variable was measured by a series of questions prepared by the teacher. Data processing was carried out by analysis of covariance (ANCOVA) using the results of the pretest as covariates. The results showed that daily physical activity could improve physical fitness (F=45.91; p<0.01) and student academic achievement (F=7.72; p<0.01). The experimental group showed better physical fitness than the control group (F=100.91; p<0.01). The experimental group also showed better academic achievement than the control group (F=19.45; p<0.01). Based on the results of the analysis, it can be said that the application of daily physical activity for 2 months is proven to be effective in improving physical fitness and academic achievement of fifth-grade students at SDN Pesanggrahan I, Kwanyar, Bangkalan.